Discordance of HER2 between primary tumors and lymph node metastatic lesions in invasive breast cancer - Nugrohowati, Noviana; Anwar, Sumadi Lukman; Juwaryani, Juwaryani; Ridhayani, Firda (Faculty of Medicine, Universitas Trisakti, 2025)
BackgroundBreast cancer therapy is mostly influenced by the type and molecular subtype, especially in the case of human epidermal growth factor receptor 2 (HER2) status, where HER2-positive patients will receive anti-HER2 therapy. HER2 status is obtained from HER2 immunohistochemistry examination which can be performed on primary breast tumors or lymph node metastatic lesions. This study aimed to determine the concordance of HER2 status between primary tumors and lymph node metastatic lesions in invasive breast cancer. MethodsA cross-sectional study was conducted involving 30 invasive breast cancer patients. HER2 immunohistochemistry examination was carried out on both the primary tumor and lymph node metastatic lesions. The Cohen κ coefficient was used to analyse the data. Results The concordance rate for HER2 was 86.67%. Thirteen cases were concordantly HER2-negative in primary breast cancer (BC) and nodal metastases, and 13 cases were HER2-positive in both primary and metastatic tumors. Changes in HER2 status between primary BC and corresponding synchronous metastases were observed in four (4.72%) cases. One of the discordant cases was HER2-negative in the primary tumor and HER2-positive in the metastases, while three cases were HER2-positive in the primary breast cancer and HER2- negative in the metastases. Conclusion There is a discordance of HER2 status between the primary tumor and lymph node metastases in invasive breast cancer patients. It is necessary to evaluate the HER2 status of the primary tumor and metastases simultaneously. Such an evaluation is recommended for better prognosis and survival.